2019
DOI: 10.3390/sym11050657
|View full text |Cite
|
Sign up to set email alerts
|

Overview of Low-Temperature Heat Capacity Data for Zn2(C8H4O4)2.C6H12N2 and the Salam Hypothesis

Abstract: The review presents the progress in the analysis of low-temperature heat capacity of the metal-organic framework Zn2(C8H4O4)2.C6H12N2 (Zn-DMOF). In Zn-DMOF, left-twisted D3(S) and right-twisted D3(R) DABCO molecules (C6H12N2) can transform into each other by tunneling to form a racemate. Termination of tunneling leads to a phase transition in the subsystem of twisted molecules. It is suggested that Zn-DMOF may be considered a model system to study the mechanisms of phase transitions belonging to the same type … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…1); the framework of this system can absorb various molecules, including atomic gases [19,20]. Since it was previously shown that the DABCO molecule has two energy degenerate quantum states corresponding to right-twisted (R) and lefttwisted (S) structural modifications [21][22][23][24][25][26][27][28], the ensemble of DABCO molecules is viewed here as an unstable subsystem. The specific heat of Zn2(BDC)2(DABCO) corresponds to the 1D one-dimensional vibrational continuum and exhibits three second-order phase transitions (PTs) and [26].…”
Section: Conditions For Observing Qze and Qaze Effects In Zn2(bdc)2(d...mentioning
confidence: 99%
See 1 more Smart Citation
“…1); the framework of this system can absorb various molecules, including atomic gases [19,20]. Since it was previously shown that the DABCO molecule has two energy degenerate quantum states corresponding to right-twisted (R) and lefttwisted (S) structural modifications [21][22][23][24][25][26][27][28], the ensemble of DABCO molecules is viewed here as an unstable subsystem. The specific heat of Zn2(BDC)2(DABCO) corresponds to the 1D one-dimensional vibrational continuum and exhibits three second-order phase transitions (PTs) and [26].…”
Section: Conditions For Observing Qze and Qaze Effects In Zn2(bdc)2(d...mentioning
confidence: 99%
“…PT1 is associated with the ordering/disordering of BDC 2anions at a phase transition point Tc ~ 130K [20]. PT2 (Tc ~ 60K) is associated with the termination of tunnelling between two energy-degenerate quantum states (R and S) of DABCO molecules; PT3 (Tc ~14K) is related to the distribution of DABCO molecules over three different energy states [21][22][23][24][25]28]. Of primary interest are low-temperature phase transitions PT2 and PT3 associated with the evolution of DABCO energy states and, consequently, with a possible occurrence of QZE/QAZE effects.…”
Section: Conditions For Observing Qze and Qaze Effects In Zn2(bdc)2(d...mentioning
confidence: 99%
“…Many essential biological and chemical processes are stereoselective, involving only one enantiomer, which exists independently from its chiral counterpart. Separation of one enantiomer from another is not only important for practical use, but also sparks much interest as a fundamental problem, which constantly attracts research attention to the spatial and electronic structure of enantiomers [1][2][3]. In particular, especially interesting is how the parity violating weak nuclear forces may manifest in chiral molecules and may be somehow responsible for the choice of which enantiomer would prevail in living organisms [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Previously, the detailed analysis of the 1,4-diazabicyclo[2.2.2]octane (DABCO) molecule with D 3S (left-twisted), D 3R (righttwisted), and D 3h (untwisted) symmetries in gas phase and in Metal-organic Frameworks (MOFs) was performed [8,9]. There were expectations that MOFs with a DABCO linker may undergo a number of phase transitions related to enantiomers ordering [2,10], and that cooperative effects in such systems may help the experimental search of molecular parity violation effects [7,9,11]. However, the energy barrier between the D 3S and D 3R states of DABCO appears to be very low (<100 J/mol in gas phase [8] and~5 kJ/mol in MOF [9]), which makes MOFs with DABCO difficult for experimental studies of such effects.…”
Section: Introductionmentioning
confidence: 99%
“…dabco, M = Co, Ni, Cu, and Zn), typical representatives of MOF compounds, have a relatively large pore size and pore volume (∼7–8 Å and ∼0.63–0.84 cm 3 /g, respectively). At room temperature, the tetragonal M-DMOF structure consists of two-dimensional layers composed of inorganic building units M 2 (O 2 C-) 4 and phenylene groups [C 6 H 4 ] of (bdc) 2– anions and of organic ligands C 6 H 12 N 2 (dabco) connecting the layers by their nitrogen atoms coordinated to metal atoms. , The tendency of M-DMOFs to undergo structural rearrangements is due to the dynamic disorder of dabco molecules, bdc 2– anions, and M 2 (O 2 C-) 4 . , Thus, Zn-DMOF was shown to undergo three phase transitions (at ∼ 15, ∼ 60, and ∼130 K) whose mechanisms were studied theoretically and experimentally. According to recent studies, Ni-DMOF possesses unique optical, magnetic, and catalytic properties. , In particular, the character of exchange interactions of nickel ions was found to depend on temperature changes . Assuming that the changes in the character of exchange interactions are related to phase transitions, the presented study aims at determining molar heat capacity, enthalpy, and entropy of Ni-DMOF in the temperature region of 5–300 K using adiabatic calorimetry.…”
Section: Introductionmentioning
confidence: 99%